Dimer ribbon structures on diamond (001) surfaces revealed with atomic force microscopy - Runnan Zhang; Yuuki Yasui; Masahiro Fukuda; Masahiko Ogura; Toshiharu Makino; Daisuke Takeuchi; Taisuke Ozaki; Yoshiaki Sugimoto (Physical Review Research)
The potential of diamond films for future semiconductor applications is partly limited by current growth techniques. This limitation can be addressed by achieving an atomic-level understanding of the growth processes. Using atomic force microscopy with atomic resolution, we examined diamond surfaces and observed specific structures, where odd numbers of dimers form ribbonlike configurations. Formed in the nonequilibrium environment of plasma, these structures were evaluated as the most stable configurations through density-functional-theory calculations. Our findings provide a crucial foundation for optimizing the film growth process.